2020
DOI: 10.1155/2020/5926381
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Quercetin as an Antiatherosclerotic Agent in Atherosclerotic Cardiovascular Disease: A Review

Abstract: Atherosclerotic cardiovascular disease (ASCVD) is one of the diseases with the highest morbidity and mortality globally. It causes a huge burden on families and caregivers and high costs for medicine and surgical interventions. Given expensive surgeries and failures of most conventional treatments, medical community tries to find a more cost-effective cure. Thus, attentions have been primarily focused on food or herbs. Quercetin (Qu) extracted from food, a flavonoid component, develops potentials of alternativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 127 publications
1
47
0
Order By: Relevance
“…( 28 ) Quercetin (3,3,4,5,7-pentahydroxyflavone; Q), a flavonol-type flavonoid commonly present in fruits and vegetables, is a potential candidate for use in preventing the onset of cardiovascular diseases owing to its anti-oxidative or anti-atherosclerosis functions. ( 29 31 )…”
Section: Introductionmentioning
confidence: 99%
“…( 28 ) Quercetin (3,3,4,5,7-pentahydroxyflavone; Q), a flavonol-type flavonoid commonly present in fruits and vegetables, is a potential candidate for use in preventing the onset of cardiovascular diseases owing to its anti-oxidative or anti-atherosclerosis functions. ( 29 31 )…”
Section: Introductionmentioning
confidence: 99%
“…Transfection of the miR-21 inhibitor eliminates the protective effect of kaempferol exerted on oxidative stress by reversing the enhanced activities of antioxidant enzymes such as SOD and attenuates iNOS activity and NO levels [ 209 ]. Quercetin is the most common and widely distributed flavonol compound, and daily consumption is realized in the form of plant-derived foods such as tea, onion, lettuce, broccoli, beans, and buckwheat [ 210 ]. Quercetin has a long history of exerting beneficial health effects, especially cardioprotective effects, and is associated with the ability to quench free radicals as antioxidants and to reduce the formation of atherosclerotic plaque [ 210 ].…”
Section: The Regulation Of Cvd-related Mirnas By Natural Antioxidamentioning
confidence: 99%
“…Quercetin is the most common and widely distributed flavonol compound, and daily consumption is realized in the form of plant-derived foods such as tea, onion, lettuce, broccoli, beans, and buckwheat [ 210 ]. Quercetin has a long history of exerting beneficial health effects, especially cardioprotective effects, and is associated with the ability to quench free radicals as antioxidants and to reduce the formation of atherosclerotic plaque [ 210 ]. The anti-inflammatory properties of quercetin include the downregulation of miR-155 enhancement of the miR-21 expression, which is one of the pro-inflammatory miRNAs [ 161 ].…”
Section: The Regulation Of Cvd-related Mirnas By Natural Antioxidamentioning
confidence: 99%
“…Quercetin is also found in fruits, nuts, and vegetables ( Stromsnes et al, 2020 ). Studies showed that quercetin has potential to treat atherosclerosis by reducing inflammation and resisting oxidative stress ( Deng et al, 2020 ). The antioxidant effects of quercetin occur first by inhibition of p47phox and p67phox activity, reducing NADPH oxidase activation to decrease ROS production ( Xiao et al, 2017 ).…”
Section: Tcm For Treatment Of Atherosclerosis Targeting Oxidative Stressmentioning
confidence: 99%